PENGARUH PENGEMBANGAN KARIR, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KELURAHAN BEKASI JAYA - Handayani, Novia; Pitoyo, Bayu Seno; Giningroem, Dewi Sri Woelandari Pantjolo (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study is conducted to determine the extent of the influence of Career Development, Work Discipline, and Work Motivation on the Performance of Employees at Bekasi Jaya Sub-district. The population of this study is all employees of Bekasi Jaya Sub-district. This research uses a quantitative method. Data collection in this study was conducted using a questionnaire with 39 respondents, and the sampling method used is non-probability sampling where the entire population is treated as a sample. The data analysis technique used is multiple linear regression analysis with the help of SPSS application. The results of the partial (t) test show that the Career Development variable does not have a significant effect on Employee Performance. Work Discipline has a significant effect on Employee Performance. And Work Motivation does not have a significant effect on Employee Performance. Furthermore, the simultaneous (f) test results show that all three variables together have a significant influence on employee performance.